Comparison of the immunological and virological responses to cART between HIV-1/O and HIV-1/M patients followed up in France - Unal, Guillemette; Seng, Rémonie; Alessandri-Gradt, Elodie; Plessis, Lorraine; Ghislain, Mathilde; Goujard, Cécile; Leoz, Marie; Plantier, Jean-Christophe; Meyer, Laurence; Duvivier, Claudine; Touam, Fatima; Pialoux, Gilles; et al. (Journal of antimicrobial chemotherapy, 2025)
Therapeutic outcomes for patients infected by genetically divergent HIV-1/O are not well-known due to scarce data and the lack of an appropriate comparison with patients infected by pandemic HIV-1/M. We aimed to compare the immunological and virological response to cART between HIV-1/O and HIV-1/M patients followed in France. All naïve HIV-1/O subjects initiating cART in France in ANRS-ORIVAO study were compared to naïve HIV-1/M subjects initiating cART in ANRS-COPANA cohort. Piecewise linear mixed-effect models and Kaplan-Meier survival curves were used to analyse immunological and virological response to cART overall (65 HIV-1/O versus 279 HIV-1/M), then only in patients initiating 2INTI + 1PI/r. Plasma viral load (pVL) at treatment initiation was 0.6 log10 copies/mL lower in HIV-1/O than in HIV-1/M patients (P = 0.004) in the overall population, but there was no difference in the time to pVL < 200 cp/mL after cART initiation (log rank test, P = 0.57). Meanwhile, baseline CD4 counts were lower in HIV-1/O (median 180/mm3) than HIV-1/M (248/mm3) patients (P = 0.001). At 4 months, the increase in CD4 counts did not differ (P = 0.96) between groups but remained lower in HIV-1/O patients beyond 4 months of treatment (P = 0.04).In PI/r population, baseline pVL was 1 log10 copies/mL lower for HIV-1/O than HIV-1/M patients, leading to significantly faster attainment of pVL < 200 cp/mL (log rank test: P < 0.001); immunological response to cART was similar. HIV-1/O and HIV-1/M immunological and virological responses to cART did not differ when epidemiological characteristics of the patients were taken into account. In France, treating HIV-1/O following HIV-1/M guidelines leads to similar therapeutic outcomes.